Telaah Kurikulum Merdeka Berdasarkan Kesesuaian dengan Tujuan Pendidikan Nasional - Tatia, Lailul; Murni, Rifa Sri; Simanjorang, Yabes Jafer Karlo; Sianturi, Royden Simbah; Hasibuan, Nasywa Humair Affandy; Pulungan, Khoirul Ikhsan; Harahap, Herlina Jasa Putri (Universitas Islam Sumatera Utara, 2025)
This study aims to analyze the alignment between the Merdeka Curriculum and the National Education Goals as stipulated in Law Number 20 of 2003 concerning the National Education System. A qualitative descriptive approach was applied through document analysis techniques, focusing on official sources such as the Merdeka Curriculum framework, the Pancasila Student Profile, and the formulation of national education objectives. The findings indicate that, conceptually, the Merdeka Curriculum has successfully integrated the core values of national education, including fostering students’ faith, independence, creativity, and their role as responsible and democratic citizens. The curriculum emphasizes student-centered learning with contextual and adaptive approaches to meet diverse educational needs. However, the achievement of these objectives largely depends on the effectiveness of implementation, particularly in relation to teacher preparedness, educational infrastructure, and consistent policy support. This study concludes that the Merdeka Curriculum holds great potential to realize Indonesia’s national education goals, yet its success requires sustainable collaboration among all educational stakeholders.